A Novel Technique of Posterolateral Suturing in Thoracoscopic Diaphragmatic Hernia Repair - Yoon Jung Boo; Stephan Rohleder; Oliver J. Muensterer (Georg Thieme Verlag KG, 2017)
Abstract Background Closure of the posterolateral defect in some cases of congenital diaphragmatic hernia (CDH) can be difficult. Percutaneous transcostal suturing is often helpful to create a complete, watertight closure of the diaphragm. A challenge with the technique is passing the needle out the same tract that it entered so that no skin is caught when the knots are laid down into the subcutaneous tissue. This report describes a novel technique using a Tuohy needle to percutaneously suture the posterolateral defect during thoracoscopic repair of CDH. Case We report a case of a 6-week-old infant who presented with a CDH and ipsilateral intrathoracic kidney that was repaired using thoracoscopic approach. The posterolateral part of the defect was repaired by percutaneous transcostal suturing and extracorporeal knot tying. To assure correct placement of the sutures and knots, a Tuohy needle was used to guide the suture around the rib and out through the same subcutaneous tract. The total operative time was 145 minutes and there were no perioperative complications. The patient was followed up for 3 months, during which there was no recurrence. Conclusion Our percutaneous Tuohy technique for closure of the posterolateral part of CDH enables a secure, rapid, and tensionless repair.